INTERNATIONALISATION OF HIGHER EDUCATION AND ITS PROVISIONS IN NATIONAL EDUCATION POLICY 2020 - Bajia, Rajendra Singh; Nagda, Ramesh Chandra (International Journal of Research -GRANTHAALAYAH, 2025)
The National Education Policy 2020 (NEP 2020) is an important effort towards transforming the education system in India according to the needs of the 21st century. This policy presents internationalisation as a key component to make higher education compatible with global standards. This research paper analyses the concept, need, current scenario of internationalisation of higher education and its various provisions in NEP 2020. Also, the opportunities and challenges facing India in this direction have also been discussed. At the end of the research, some important suggestions have been presented for the effective implementation of the policy. This study may prove useful for education policy makers, researchers, academicians and all stakeholders who want to understand the implications of the policy.